Historical biogeography of the tribe Platypleurini Schmidt, 1918 (Hemiptera: Cicadidae) with a focus on Southern Africa - Price, Benjamin Wills (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2010)
With our contemporary biota under increasing threat of extinction, it is of interest to understand where, why and how biological diversity is generated. If focussed on appropriate taxa, phylogeographic and phylogenetic studies can assist in the identification of both places and processes central to the origin and maintenance of biological diversity. It is explained why southern Africa presents a perfect test-bed for exploring such mechanisms of diversification and why cicadas (Hemiptera: Cicadidae) have proved very suitable tools for studies of historical biogeography. This study then exemplifies these points by providing the first large-scale investigation of the historical biogeography of the tribe Platypleurini Schmidt, 1918, with emphasis on the genus Platypleura Amyot & Seville, 1843 in southern Africa. Standard methods of DNA sequencing provided data from portions of the mitochondrial small subunit ribosomal 16S RNA (16S) and cytochrome oxidase subunits I (COI) and II (COII); and the nuclear elongation factor 1 alpha (EF-1Î±) from 400 ethanol-preserved specimens. These data were analysed using standard phylogenetic methods and a time scale of diversification was estimated using a Bayesian framework and both fossil data and DNA substitution rates. The results showed that the tribe is too recent to be of Gondwanan origin. The lack of monophyly of the genera represented in both Asia and Africa showed that the tribe needs formal taxonomic revision. Diversification of the African platypleurine genera coincides with aridification in the early Oligocene. Dispersal of Asian platypleurine taxa coincides with the meeting of Africa and Eurasia in the mid-Oligocene. Two radiations within African Platypleura are hypothesised; one distributed over most of sub-Saharan Africa and the second restricted to southern Africa, with clades restricted within regional biomes. Within each of the three focal biomes, cryptic taxonomic diversity was confirmed, suggesting that, even in relatively well understood groups such as the southern African platypleurine cicadas, molecular data can identify further diversity. Although each focal taxon was restricted to non-overlapping biomes, comparison of the three biomes highlighted interactions between palaeoclimates and fixed landscape features (coastal topography, river catchments and escarpments) as causative agents of vicariance, dispersal, extinction and diversification of these volant insects. The results of using co-distributed species for comparative study cautions against making inferences based on single-taxon datasets and highlights the need to use many, evolutionarily independent taxa when identifying mechanisms of diversification. The dating analyses imply that within-species lineage diversification occurred overwhelmingly within the Pleistocene, a trend that is being increasingly recognised in print for other biota. Some caveats about using phylogenetic approaches to estimate ancestral areas are illustrated. Several recommendations are made regarding additional taxa and data sources for understanding the origin and maintenance of biological diversity.
Keywords: Biogeography -- History -- Africa, Southern; Cicadas -- Africa, Southern; Cicada (Genus) -- Africa, Southern; Biodiversity -- Africa, Southern; Cicadas -- Variation -- Africa, Southern